Numerical study of monomer-monomer reactions on composite catalysts: well-mixed species model - Katauskis, Pranas; Sakalauskas, Justas (Lietuvos matematikos rinkinys, 2015)
A nonlinear mathematical model describing the kinetics of a bimolecular heterogeneous catalytic reaction proceeding on a supported catalyst is studied. The model is based on the Langmuir–Hinshelwood surface reaction mechanism assuming that all species are well-mixed. The catalytic surface size influence on the catalytic reactivity and product concentration is investigated numerically for different arrangements of the adsorption sites.
Keywords: surface reaction; adsorption; desorption; spillover